Beauveria bassiana as an artificial endophyte in tissuecultured banana (Musa spp.) plants: a novel way to combat the banana weevil Cosmopolites sordidus - Akello, J.; Dubois, T.; Coyne, Danny L.; Hillnhűtter, C. (2008)
Beauveria bassiana, which is effective against a variety of insect pests, is the most researched and commercialised fungal biopesticide. Laboratory and screenhouse studies have revealed great potential of this entomopathogenic fungus for use against the banana weevil, Cosmopolites sordidus, in banana. However, impractical field delivery methods and high costs associated with the application of B. bassiana against C. sordidus prevent its use and commercialisation in banana fields. Our research has revealed that B. bassiana can colonise internal banana tissues for at least four months after tissue-cultured plantlets are dipped in a spore suspension. The type of banana cultivar did not affect colonisation by Beauveria bassiana and, even when elevated B. bassiana doses were used, plant growth was not reduced. In a set of three screenhouse experiments, larval mycosis rates in B. bassiana-treated plants were 23.5-88.9% and the presence of the fungus inside treated plants led to a reduction in larval damage of up to >50%. Application of B. bassiana as an artificial endophyte inside banana plants could circumvent bottlenecks associated with its application as a conventional biopesticide, because i) it kills the damaging larval stages inside the plant, ii) it is protected from adverse biotic and abiotic factors, iii) little inoculum is required, drastically reducing its cost, and iv) farmers do not need to apply the biological control organism themselves, as the technology is easily transferable to a commercial tissue culture producer.